2011
DOI: 10.1142/s0217984911027157
|View full text |Cite
|
Sign up to set email alerts
|

THE FIRST PRINCIPLES CALCULATION OF STRUCTURAL, ELECTRONIC AND MAGNETIC PROPERTIES OF MnXY (X = Ru, Rh AND Y = Ga, Ge, Sb) ALLOYS

Abstract: The structural, electronic and magnetic properties of MnXY ( X = Ru , Rh and Y = Ga , Ge , Sb ) Heusler alloys are studied using density functional theory by the WIEN2k package. These materials are ferromagnetic. Also they have some interesting half-metallic properties. The electron density of states, total and local magnetic moment of these alloys are calculated. We have calculated the effective Coulomb interaction U eff using the ab initio method. We have compared the magnetic moments of these alloys in GGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The integration over the Brillouin zone (BZ) was considered by taking a dense k mesh of 12 × 12 × 12 k points [33] and the self-consistency convergence criteria of 10 −10 Ry was considered. The details of U calculation can be found in previous work [10,25,34,35] and U values for these atoms were found to be 1.90 eV, 2.50 eV, and 0.90 eV for Ru, Fe, and Cr, respectively. The mechanical and dynamical stabilities were calculated using the thermo_pw package interfaced with the QE package [36].…”
Section: Computational Detailsmentioning
confidence: 89%
See 1 more Smart Citation
“…The integration over the Brillouin zone (BZ) was considered by taking a dense k mesh of 12 × 12 × 12 k points [33] and the self-consistency convergence criteria of 10 −10 Ry was considered. The details of U calculation can be found in previous work [10,25,34,35] and U values for these atoms were found to be 1.90 eV, 2.50 eV, and 0.90 eV for Ru, Fe, and Cr, respectively. The mechanical and dynamical stabilities were calculated using the thermo_pw package interfaced with the QE package [36].…”
Section: Computational Detailsmentioning
confidence: 89%
“…Ishida et al examined the electronic properties of RuMnZ (Z = Si, Ge and Sn) compounds and found them to be HM ferromagnets [24]. An electronic and magnetic study was done by Moniri et al on MnYZ (Y = Ru, Rh and Z = Ga, Ge and Sb) compounds using local gradient approximation (LDA), GGA and LDA + U [25]. The compounds HfYSb (Y = Co, Rh and Ru) were found to be mechanically stable in the pressures range of 0 to 60 GPa with HfRuSb showing metallic character [26].…”
Section: Introductionmentioning
confidence: 99%
“…The total density of states (TDOS) and partial density of states (PDOS) of HH's were calculated within GGA + Hubbard potential (GGA + U) and mBJ approximation from À15 to 10 eV. The Hubbard potential (U eff ) values of Ti, Ru, and Pt used to calculate the electronic properties of HH's are 5.0, 1.9, and 2.9 eV, respectively[27][28][29]. On the other hand, these properties of the DHH compound are determined from TB-mBj approximation along high-symmetry points (HH: W-L-Γ-X-W-K, DHH: Z-Γ-X-P-Γ-N) in the first Brillouin-zone (BZ) as illustrated in…”
mentioning
confidence: 99%